LINGUISTIC ERRORS IN LEGAL TEXTS - Nurbayeva, Нуркиз Арысбекқызы (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2024)
The language of the law encompasses lexical, syntactic, and stylistic elements that shape the text of a law or other normative legal act. Requirements for the language of the law are considered during the drafting of a bill. However, in the process of legislative work, complete elimination of linguistic errors from the text is not always achievable. Such errors often include lexical and stylistic inaccuracies. The subject of the article is certain legal texts analyzed from a linguistic standpoint as part of fundamental and applied research on the topic "Monitoring Compliance with Content and Style Requirements in the Laws of the Republic of Kazakhstan." The relevance of the article lies in identifying and rectifying errors in the text of current legislation, determining gaps that lead to a distortion of the meaning of the main legal norms, and exploring ways to prevent such distortions. The author presents specific examples of typical linguistic errors of lexical, grammatical, and stylistic nature, as well as others found in the texts of current legislation. An analysis is conducted of regulatory proposals and legal norms to assess their conformity with the norms and rules of modern Kazakh literary language. While examining the texts of current laws, the author believes it is necessary to conduct comprehensive monitoring of current legislation to ensure high-quality content of legal acts; to develop a compendium of rules for the use of legal terminology to standardize terms; to create conditions for the development of research on legal technology across various legal domains; and to introduce into the educational process of universities the study of relevant legal and linguistic disciplines such as "Language and Law" and "Legislative Technique" in the form of courses or specialized courses.